PERMIAN GASTROPODS FROM THE KULOGORY FORMATION OF THE NORTHERN MOSCOW SYNECLISE - Mazaev A.V. (My University, 2006)
Permian gastropods from the Kulogory Formation (Sakmarian) were studied based on the author's material and the collection of Yakowlew (Central Research Geological Prospecting Museum (TsNIGR Museum), St. Petersburg). Lectotypes for Arribazona tschernyschewi (Yakowlew, 1899) and Microdoma kulogorae (Yakowlew, 1899) were designated. Six species are described; four of them are new and two are assigned to the new genera (Biarmeaspira verideclinata gen. et sp. nov., Globodoma yakowlewi gen. et sp. nov., Glabrocingulum (Glabrocingulum) stankovskyi sp. nov., and Euconospira? pinegensis sp. nov.). The high degree of polymorphism in the dominant species of uniform assemblages is probably the result of their development in "undersaturated" paleocommunities of closed lagoons with gradually increasing concentration of sulfate ions. © Pleiades Publishing, Inc. 2006.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская